Developing Socio-Cultural Competence in Art Education Through Analysis of Artworks - Toshmuhammedova Iroda Alibek qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores methods for developing socio-cultural competence in students through the analysis of artworks in art education. By examining historical and contemporary art, students gain an understanding of cultural values, social contexts, and artistic techniques. The study emphasizes pedagogical approaches, including interactive analysis, project-based learning, and reflective discussion, to enhance creative thinking, aesthetic competence, and cultural awareness.